Design and synthesis of small molecule-conjugated photoaffinity nanoprobes for a streamlined analysis of binding proteins. Issue 19 (15th October 2018) - Sakurai, Kaori; Kato, Amane; Adachi, Keisuke
Graphical abstract: Highlights: Novel small molecule-conjugated photoaffinity nanoprobes have been synthesized. A hydrophilic spacer promoted the water dispersibility of the nanoprobes. Arylazide on nanoprobes enabled a most selective crosslinking of a model binding protein. Abstract: We designed and synthesized a set of photoaffinity nanoprobes, which multivalently display a small molecule ligand and a photoreactive group on gold nanoparticles. Due to the typically hydrophobic nature of these two functional groups, a hydrophilic spacer was additionally introduced to co-functionalize the nanoprobes to maintain their dispersibility in aqueous buffer solutions. Photoaffinity labeling studies using the nanoprobes composed of different ratios of three functional groups showed that including high density of the spacer group attenuates crosslinking efficiency. Comparative analysis of the reactivity among three major photoreactive groups suggested that unlike in the context of conventional photoaffinity probes, arylazide group enables the most selective crosslinking of a model small molecule binding protein.